A survey of the library services and facilities in Quezon City public elementary and secondary schools for students with disabilities - Mercurio, Hazel C.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Since the Department of Education (DepEd) is currently strengthening its Special Education (SPED) programs by democratizing access to public education services for the less fortunate citizens of the Philippines, an assessment of the library facilities and services has to be conducted to make necessary changes to meet the special needs of its clientele. The study aims to determine the status and condition of the library services and facilities in public schools offering elementary and secondary education for children with disabilities in Quezon City.
The study used questionnaires that were patterned after the study of Arciga (1981). This is to determine whether there is an existing library in the school and whether the library complies with the guidelines in terms of accessibilities, services, and media formats for students with disabilities. Thus, personal visits were conducted to observe the library activities, programs, and services. Aside from the librarians, most of the respondents were the teacher-librarians or school personnel assigned to the public school libraries. Moreover, in order to understand the perception and activities conducted by the teachers in connection with the library services, up to ten percent (10) of the population of SPED educators in each school or SPED center were randomly selected and a questionnaire was administered. Convenience sampling was used as a method for selecting the sample.
The data gathered revealed that most of the Quezon City public school libraries were not ready to accommodate students with disabilities and the library services currently available were only for their regular students. The principal findings of the study were: (a) some of the school libraries were not accessible for the students with disabilities; (b) the public school libraries had inadequate furniture and equipment to cater to the needs of students with disabilities; (c) there were small numbers of assistive technologies for the special need of the students with disabilities; out of sixteen schools, twelve were provided computers but not all function well; (d) public school did not have guidelines to follow regarding tier library services either for the regular students or for their students with disabilities, and; (e) most of the Quezon City public school libraries improved their ventilation, light, and other physical facilities for more convenient working area for the students - regular or with disabilities; however, the book collections of the school libraries were outdated.
It is recommended that the school libraries should begin in understanding the educational pattern or the school curriculum, mission, vision, and objectives school itself or the Department of Education. Moreover, additional budget from the school administrators, Department of Education, and government should be provided in order to improve library facilities, services, and collections for students with disabilities.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- Services to the people with disabilities -- Philippines -- Quezon City; Public schools -- Philippines -- Quezon City